Wykorzystanie darmowego oprogramowania do celów zawodowych przez pracowników łódzkich bibliotek uczelnianych - Majewska, Paulina; Niezabitowska , Sylwia (Acta Universitatis Lodziensis. Folia Librorum, 2010)
The article discusses open source software, which is software that is freely made available to users with the intention of allowing the programming community to collaboratively improve it. It is also about free software, which is software that can be used without paying, but the users cannot make any changes in it. The article describes how those two types of software can be useful in academic libraries. Librarians believe that open source software and free software can be a huge help for them. This article presents results of research made in academic libraries in Lodz (Poland).